Matrix [compact disc, unabridged] - Groff, Lauren (Penguin Audio, 2021)
Cast out of the royal court by Eleanor of Aquitaine, deemed too coarse and rough-hewn for marriage or courtly life, seventeen-year-old Marie de France is sent to England to be the new prioress of an impoverished abbey, its nuns on the brink of starvation and beset by disease. At first taken aback by the severity of her new life, Marie finds focus and love in collective life with her singular and mercurial sisters. In this crucible, Marie steadily supplants her desire for family, for her homeland, for the passions of her youth with something new to her: devotion to her sisters, and a conviction in her own divine visions. Marie, born the last in a long line of women warriors and crusaders, is determined to chart a bold new course for the women she now leads and protects. But in a world that is shifting and corroding in frightening ways, one that can never reconcile itself with her existence, will the sheer force of Marie's vision be bulwark enough?